Barriers to telepsychiatry in the geriatric Asian American population during COVID-19 - Wang , Jami; Kato , Brian; Agustines, Davin A. (Journal of Ideas in Health, 2022)
Due to the increase in anti-Asian discrimination during COVID-19, there has been a decline in mental health in the Asian community, particularly in the geriatric population. Although the current literature tends to focus on the underutilization of telemedicine in the Asian American population due to cultural barriers, our research found that the barrier to access heavily contributed to this inequity. In this study, we discuss the limited language options for the geriatric Asian American population on a few large telepsychiatry platforms, including “Teladoc and BetterHelp”, during COVID-19. .